Determining Thermal Conductivity of Small Molecule Amorphous Drugs with Modulated Differential Scanning Calorimetry and Vacuum Molding Sample Preparation - Karl, Maximilian (Pharmaceutics, 2019)
Thermal conductivity is a material specific property, which influences many aspects of pharmaceutical development, such as processing, modelling, analysis, and the development of novel formulation approaches. We have presented a method to measure thermal conductivity of small molecule organic glasses, based on a vacuum molding sample preparation technique combined with modulated differential scanning calorimetry. The method is applied to the two amorphous model compounds indomethacin and celecoxib. The measured values of below 0.2 W/m °C indicate very low thermal conductivity of the amorphous compounds, within the range of organic liquids and low conducting polymers.